Synthesis of Novel (S)-Imidazolo[1,2c][1,2,3]triazolo-[4,5e]pyrimidine Derivatives - Shashidhar Reddy1, S.; George Vineel1, B.; Venkataiah1, S.; Naidu2, A.; Dubey2, P.K. (Asian Journal of Chemistry, 2014)
Isopropyl azide (1) was reacted with cyanoacetamide (2) in the presence of sodium ethoxide to obtain 4-amino-3-isopropyl-3H-[1,2,3]triazolo-5-carboxamide (3) which on treatment with excess of diethyl carbonate and sodium ethoxide gave 3-isopropyl-3H-[1,2,3]triazolo[4,5-d]pyrimidine-5,7-diol (4). The latter on treatment with POCl3 and 2,6-lutidine in the presence of catalytic amount of PCl5 resulted in 5,7-dichloro-3-isopropyl-3H-[1,2,3]triazolo[4,5-d] pyrimidine (5) in good yields. Compound 5 on condensation with L-prolinol (6) in ethanol yielded (S)-[1-(5-chloro-3-isopropyl-3H-[1,2,3]triazolo[4,5-d]pyrimidine-7-yl)pyrrolidine-2-yl-methanol (7). Compound 7 on treatment with anilines (8a-8j) gave (S)-(1-(3-isopropyl-5-(arylamino)-3H-[1,2,3]triazolo[4,5-d]pyrimidine-7-yl)pyrrolidine-2-yl) methanol (9a-j) by the nucleophilic displacement of the chlorine at 5th-position. 9a-j on treatment with POCl3 afforded a series of novel chiral derivatives of (S)-N-(3-isopropyl-7a,8,9,10[1'2':3,4]imidazolo[1,2c][1,2,3]triazolo[4,5e]pyrimidine5(7H)yl-idine) aniline hydrochloride (10a-j) by dehydrative cyclization. This cyclization also takes place with SOCl2 under refluxing conditions, but yields are low compared to the POCl3 conditions.